The crucial role of 5hmC in neuroprotection and repair after cerebrovascular injury - Yanina Tsenkina (Academia Biology)
Cerebrovascular injuries, such as stroke and other vascular insults to the brain, present significant challenges to neurological function and recovery. Within the complex realm of epigenetic modifications, hydroxymethylation emerges as a crucial factor in orchestrating mechanisms for neuroprotection and repair following such injuries. This review consolidates current research on the multifaceted role of 5-hydroxymethylcytosine (5hmC) in regulating molecular and cellular processes vital for neuronal survival and regeneration after cerebrovascular injury. The discussion delves into the dynamic interaction between hydroxymethylation and important pathways in neuroprotection, such as the modulation of excitotoxicity and cellular metabolism, resolution of inflammation, and mitigation of oxidative stress. Additionally, it explores emerging evidence suggesting that 5hmC contributes to neurorepair by promoting neurogenesis, axonal regeneration, angiogenesis, and synaptic plasticity. Understanding the role of hydroxymethylation in cerebrovascular injury provides insights into potential therapeutic approaches for enhancing the brain’s innate mechanisms for protection and repair. By elucidating the intricate involvement of 5hmC in these injuries, this review establishes a basis for further research aimed at leveraging its therapeutic potential to alleviate neurological deficits and promote recovery in affected individuals.